2007
DOI: 10.1016/j.ijrobp.2006.12.058
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Motion of The Heart and Positional Reproducibility Under Active Breathing Control

Abstract: Purpose-To reduce cardiotoxicity from breast radiotherapy (RT), innovative techniques are under investigation. Information about cardiac motion with respiration and positional reproducibility under active breathing control (ABC) is necessary to evaluate these techniques.Methods-Patients requiring loco-regional RT for breast cancer were CT-scanned using an ABC device at various breath-hold states, before and during treatment. Ten patients were studied. For each patient, 12 datasets were analyzed. Mutual informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(41 citation statements)
references
References 27 publications
1
39
0
1
Order By: Relevance
“…The reported discrepancy was 0.2±0.19 cm, which was fairly reproducible. On the other hand, it was reported that the interfraction DIBH motion of the heart had reproducibility of 3 mm in the anterior–posterior (AP), 7 mm in the superior–inferior (SI), and 3 mm in the left–right (LR) directions (24) . Moderate correlation was found between surface and heart setup errors in Alderliesten et al: (13) normalR2=0.53, 0.37, 0.64 in AP, SI, and LR directions, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The reported discrepancy was 0.2±0.19 cm, which was fairly reproducible. On the other hand, it was reported that the interfraction DIBH motion of the heart had reproducibility of 3 mm in the anterior–posterior (AP), 7 mm in the superior–inferior (SI), and 3 mm in the left–right (LR) directions (24) . Moderate correlation was found between surface and heart setup errors in Alderliesten et al: (13) normalR2=0.53, 0.37, 0.64 in AP, SI, and LR directions, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…These are valid measures to analyze interfraction motion; however, they cannot provide residual intrafraction motion during beam‐on. Jagsi et al (15) reported displacements (3 mm in AP and 6 mm in SI) of LAD position under shallow breathing states using active breathing control and the images were acquired at the time of the CT simulation. Moran et al (5) also used CT‐simulation images to study the short‐term displacement and reproducibility of the breast or chest wall and nodal regions at different breath‐hold states using ABC, in which −4 of reproducibility was observed.…”
Section: Discussionmentioning
confidence: 99%
“…The RP technology requires execution of radiotherapy in certain parts of the breathing cycle to exclude OAR and target displacement [19,21,22]. RP is used to tailor treatment plan, considering breath cycle-related movement and anatomic changes in target and neighboring tissues; planning and treatment that were done based on I images contributes heart protection in breast carcinoma [19,21,22].…”
Section: Discussionmentioning
confidence: 99%
“…The ventricles and atria volumes differ correspondingly to circulation causing intrinsic heart motion. It was shown that, although there was a large displacement, heart shape changed slightly during breath cycle [22]. Since heart is a relatively flexible organ and has intrinsic motion, it constitutes images like oscillations on MR and CT images.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation